Study of some Vitality characteristics of infectious bronchitis virus strains isolated from chicken flocks in Syria - عبد العزيز فهيم; سلهب محمد; ديب العمر أنور; مسالمة محمد; الجلاد تماره (Latakia University Journal -Biological Sciences Series, 2021)
It is isolated 10 Infectios bronchitis virus (IBV) strains from broiler flocks that has been given symbols Tj-1…..Tj-10(Tj-1, Tj-2,Tj-3, Tj-4, Tj-5, Tj-6, Tj-7, Tj-8, Tj-9, Tj-10) through period 2018-2019 , and identified their types by NestedRT-PCR reaction. Pathogenesis of specific pathogen free (SPF) embryonated eggs inoculated with isolated strains included changes in the fetal membranes, including: hemorrhage, necrotic spots, fetal growth retardation (stunting), twisting and twisting of fetuses and legs, and a mortality of 15 % . Whereas, the pathogenicity study of isolated strains after infection by instillation in the ear and eye at a dose of 0.2 ml each, in unvaccinated local chickens, 43 weeks of age, showed the characteristic symptoms of infectious bronchitis. These included: decreased feed intake, depression and general weakness, coughing, sneezing or gasping, after an incubation period ranging between 2-3 days of experimental infection. The mortality rate was 10%. The histopathology of the dead birds did not reveal the characteristic changes of IBV. The pathogenicity of the strains isolated from broiler chickens (Tj-1… Tj-10) did not differ from each other in the clinical manifestations or anatomical lesions. To study the immunological properties of isolated strains (Tj-1-Tj-10), native (local) chickens at 21 weeks of age, not vaccinated at all, were immunized by injecting the substance containing the previously prepared virus as mentioned in the materials and methods, at a dose of 0.2 ml in the nose, and a dose of 0.2 ml in the eye. The level of immune response to these strains was determined in birds by measuring the antibody criterion in the enzyme-linked immunoassay (ELISA) test. The level of antibodies in blood serum ranged between 7939-14026 after 14 days of immunization, and between 3189-8453 after 21 days of immunization.